Triggering of Erythrocyte Cell Membrane Scrambling by Emodin - Morena Mischitelli; Mohamed Jemaà; Mustafa Almasry; Caterina Faggio; Florian Lang (Cellular Physiology and Biochemistry, 2016)
Background/Aims: The natural anthraquinone derivative emodin (1,3,8-trihydroxy-6-methylanthraquinone) is a component of several Chinese medicinal herbal preparations utilized for more than 2000 years. The substance has been used against diverse disorders including malignancy, inflammation and microbial infection. The substance is effective in part by triggering suicidal death or apoptosis. Similar to apoptosis of nucleated cells erythrocytes may enter suicidal erythrocyte death or eryptosis, characterized by cell shrinkage and cell membrane scrambling with phosphatidylserine translocation to the erythrocyte surface. Signaling involved in the triggering of eryptosis include increase of cytosolic Ca2+ activity ([Ca2+]i), oxidative stress and ceramide. The present study aimed to test, whether emodin induces eryptosis and, if so, to elucidate underlying cellular mechanisms. Methods: Phosphatidylserine abundance at the cell surface was estimated from annexin-V-binding, cell volume from forward scatter, [Ca2+]i from Fluo3-fluorescence, ROS formation from DCFDA dependent fluorescence, and ceramide abundance utilizing specific antibodies. Results: Exposure of human erythrocytes for 48 hours to emodin (≥ 10 µM) significantly increased the percentage of annexin-V-binding cells, and at higher concentrations (≥ 50 µM) significantly increased forward scatter. Emodin significantly increased Fluo3-fluorescence (≥ 10 µM), DCFDA fluorescence (75 µM) and ceramide abundance (75 µM). The effect of emodin on annexin-V-binding was significantly blunted but not abolished by removal of extracellular Ca2+. Conclusions: Emodin triggers phospholipid scrambling of the erythrocyte cell membrane, an effect at least in part due to stimulation of Ca2+ entry and paralleled by oxidative stress and ceramide appearance at the erythroctye surface.